The Influence of Capital Market Education, Investment Motivation and Technological Advances on the Interest in Sharia Stock Investment : (Case Study at Investor PT. RHB Sekuritas Indonesia Aceh Representative Office) - M. Rinaldi Saputra; Cut Dian Fitri; Azimah Dianah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Along with the increase in the number of investors from year to year, it causes the level of public interest in investing to also increase. Investment is one of the important roles for economic progress. Advancing the economy in Aceh, one of which is developing investment activities. The interest in investing in Islamic stock investors is allegedly influenced by several factors such as capital market education, investment motivation, and technological advances. This research aims to determine the influence of capital market education, investment motivation, and technological advances on the interest in Islamic stock investment. This research uses a quantitative approach. The results of the study show that: (1) Partial capital market egriation does not affect the interest in sharia stock investment (2) Partial investment motivation does not affect the interest in sharia stock investment (3) While technological advances partially affect the investment interest in Islamic stocks (4) Simultaneously All three of them both influence the interest in Sharia stock investment.